PENGARUH RAZIA LAPANGAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DALAM MENUNJANG PENCAPAIAN TARGET PADA UPTP SAMSAT WILAYAH GOWA - Burhan, Imron; Sari Den Ka, Veronika; Ilham, Ilham; Nirmala Sari, Sri; Arifin, Rukhminih; Nur’Aeni, Nur’Aeni (Jurnal Analisa Akuntansi dan Perpajakan, 2024)
Taxpayer compliance are inspections carried out jointly on the highway by members of the police for efficiency and effectiveness in order to avoid repeated inspections and harm the community (Wulandari, M., & Sulistyowatie, S, 2017), by conduction inspections against taxpayers, besides that field raids are carried out in order to narrow the movement of vehicle tax arrears. This study aims to determine the effect of inspection raids on vehicle tax on taxpayer compliance in paying vehicle taxes as a support for achieving targets at UPTP SAMSAT Gowa Region. In this study using quantitative methods. The data used in this study are primary and secondary data with data collection techniques by using a questionnaire. Samples in this study is 183 community populations who were caught by inspection in Gowa Regency. The data analysis technique used simple linear regression analysis using SPSS 20. Result of the study showing that inspection had a significant effect on taxpayer compliance. Taxpayer compliance will continue to increase when enforced inspection regulary.